The Analysis of Lateral Violence among Nurses in Accredited Hospital in Riau Province - Fitra Mayenti; Dilgu Meri (Universitas STRADA Indonesia, 2022)
Background: Violence in the workplace affects the performance of nurses in providing nursing care. In addition, it can increase absenteeism, influence nurses' personal and professional lives, increase administrative stress and distrust, and increase staff burnout and turnover. Purpose: This study aims to analyze lateral violence in hospital nurses. Methods: The type of research used in this research is quantitative research with a descriptive approach. This research was conducted at an accredited hospital in Pekanbaru, in January 2019. Results: The sample of the study was nurses in the room with a total of 50 respondents and the data were analyzed univariately. Conclusion: The results of the study were obtained at Petala Bumi Hospital, as many as 100% of respondents: often treated politely and respectfully by co-workers, lateral violence from co-workers in the hospital is not a problem, the seriousness of a problem regarding lateral violence by co-workers is very serious category, never lose patience and become rude to coworkers, workload is a major cause of stress related to inadequate staff and resources to deal with while at Syafira Hospital Pekanbaru as many as 80% of respondents are often treated politely and respectfully by co-workers, 48% of respondents are lateral violence from co-workers in a large hospital or caused by many people, 36% of respondents are serious about a problem about lateral violence by co-workers very serious category, 48% of respondents sometimes lose their temper and become rude to coworkers, 64% of respondents workload the main cause of stress is related to inadequate staff and resources to deal.